2017
DOI: 10.1111/aor.12874
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of a Novel Puborectalis-Like Artificial Anal Sphincter

Abstract: Artificial anal sphincter (AAS) is an in situ implanted device that acts as a treatment for fecal incontinence regardless of etiology by augmenting the incompetent sphincteric structures. However, AAS is impeded from becoming a valid therapy by its high rate of ischemic complication and malfunction. This article presents an original puborectalis-like artificial anal sphincter (PAAS) that features a low risk of ischemia necrosis and rectal perception remodeling. The device retains continence by reproducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The use of actuators is less developed but recent research highlights their promise to address and transform areas where no solution exists, particularly in FI. Key examples include a smart biomimetic sphincter using electroactive-polymers (EAPs) (84) and a novel artificial sphincter using active pressure control to prevent tissue erosion (85).…”
Section: Smart Systemsmentioning
confidence: 99%
“…The use of actuators is less developed but recent research highlights their promise to address and transform areas where no solution exists, particularly in FI. Key examples include a smart biomimetic sphincter using electroactive-polymers (EAPs) (84) and a novel artificial sphincter using active pressure control to prevent tissue erosion (85).…”
Section: Smart Systemsmentioning
confidence: 99%
“…Jin et al of the Shanghai Jiao Tong University, Shanghai, China reported on a puborectalis‐like artificial anal sphincter (PAAS). The device retains continence by reproducing the action, including the pulling and angulating the rectum, of the puborectalis muscle, which forms the anorectal angle and reduces the required clamping pressure.…”
Section: Biomaterials and Biomechanicsmentioning
confidence: 99%
“…However, after a 3‐week in vivo test among four swines, several defects of PAAS occurred and need to be addressed, especially in the PSS. Those defects are listed as follows: In previous PAAS, there are prosthetic sphincters, power supply unit (PSU), and TET receiver coil that need to be implanted . Therefore, the time cost to complete the surgery of implantation is long, which may result in infection due to long time exposing of organs to air.…”
Section: Introductionmentioning
confidence: 99%
“…1. In previous PAAS, there are prosthetic sphincters, power supply unit (PSU), and TET receiver coil that need to be implanted 25 . Therefore, the time cost to complete the surgery of implantation is long, which may result in infection due to long time exposing of organs to air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation